2008
DOI: 10.1039/b810008j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of DNA containing a spore photoproduct analog

Abstract: The spore photoproduct is a unique photolesion, formed in spores upon irradiation with UV light; to investigate the properties of spore photoproduct containing DNA we have synthesized 5S and 5R lesion analogs and incorporated them into DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Together with previous synthetic results from our laboratory, which show incorporation of the backboneopened 3'!5' 5S and 5R lesion analogues, the whole set of the 4 possible spore lesions can now be prepared and inserted into DNA. [8] Repair studies show that the 5'!3' 5R analogue, incorporated in oligonucleotides, is efficiently repaired. Crystallization of a DNA duplex containing the 5'!…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with previous synthetic results from our laboratory, which show incorporation of the backboneopened 3'!5' 5S and 5R lesion analogues, the whole set of the 4 possible spore lesions can now be prepared and inserted into DNA. [8] Repair studies show that the 5'!3' 5R analogue, incorporated in oligonucleotides, is efficiently repaired. Crystallization of a DNA duplex containing the 5'!…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported the synthesis of 3'!5' lesion analogues with 5S and 5R configurations as phosphoramidite building blocks and showed the preparation of DNA duplexes containing both compounds. [8] The 5S isomer was indeed found to create the more stable duplex proving that the 3'!5' reaction would form preferentially the 5S-configured lesion. Initial studies with a dinucleotide building block provided evidence that the Spl is able to repair the 5S compound.…”
Section: Introductionmentioning
confidence: 96%
“…The lower rate of turnover for synthetic dinucleoside SP relative to SP generated by UV irradiation of plasmid DNA is not surprising, as the synthetic SP is not constrained to the conformation found in a DNA strand, and also lacks the phosphodiester bridge and oligonucleotide strand that likely contribute considerably to substrate binding interactions in the SPL active site. We have incorporated the protected SP phosphotriester described in the Supporting Information into an oligo, however our initial assays on this indicated that the enzyme cannot repair the di-SEM protected SP analog, Carell has also incorporated a synthetic SP analog into an oligonucleotide strand, however the analog contains numerous protecting groups and no phosphodiester linkage; no assay data on the resulting oligos were presented 16. We are currently pursuing deprotection of the SP phosphotriesters (S.I.)…”
mentioning
confidence: 99%
“…It was found that both isomers were destabilising, but the 5R isomer more so. 215 A study of short AT hairpin structures used for the formation of thymine dimers revealed that formation is highly sequence dependent as well as dependent on the position of the T-T step. 216 Pyrimidine dimer formation has been used as a method of chemical ligation of oligonucleotides.…”
Section: Oligonucleotides Containing Modified Sugarsmentioning
confidence: 99%